2022
DOI: 10.23886/ejki.10.132.18-25
|View full text |Cite
|
Sign up to set email alerts
|

Uji Validitas dan Reliabilitas Kuesioner Sindrom Terowongan Karpal Boston Versi Bahasa Indonesia

Abstract: Kuesioner Sindrom Terowongan Karpal Boston (KSTK-B) merupakan kuesioner dalam dikembangkan dalam Bahasa Inggris untuk menilai derajat keparahan dan status fungsional pada Sindrom Terowongan Karpal(STK). Penelitian ini bertujuan untuk mendapatkan kuesioner KSTK-B versi bahasa Indonesia yang valid danreliabel. Dilakukan adaptasi dan penerjemahan transkultural KSTK-B ke bahasa Indonesia, dilanjutkan ujivaliditas menggunakan uji korelasi Pearson dan uji reliabilitas menggunakan nilai alpha Cronbach. Penelitiandila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Before the intervention (pre-test) and after the intervention (post-test), participants were assessed for their CTS symptoms and functional status using a self-reported Boston Carpal Tunnel Syndrome Questionnaire (BCTSQ), which comprises two scales, namely the Symptom Severity Scale (SSS) and the Functional Status Scale (FSS). 12 Octaviana et al 13 have confirmed the reliability and validity of the Indonesian version of BCTSQ. The SSS consists of 11 questions evaluating CTS symptoms, and the FSS has eight questions to assess the well the patient can perform activities of daily living (functional status).…”
Section: Introductionmentioning
confidence: 89%
“…Before the intervention (pre-test) and after the intervention (post-test), participants were assessed for their CTS symptoms and functional status using a self-reported Boston Carpal Tunnel Syndrome Questionnaire (BCTSQ), which comprises two scales, namely the Symptom Severity Scale (SSS) and the Functional Status Scale (FSS). 12 Octaviana et al 13 have confirmed the reliability and validity of the Indonesian version of BCTSQ. The SSS consists of 11 questions evaluating CTS symptoms, and the FSS has eight questions to assess the well the patient can perform activities of daily living (functional status).…”
Section: Introductionmentioning
confidence: 89%